Kopi Boy Employee Service Strategy - Kusumaningrum, Anisa Putri; Sugiono, Edi; Pradini, Gagih; Hibatullah, Muhammad Rafif (International Journal of Education, Information Technology, and Others, 2025)
This research explores the impact of Kopi Boy's service approach, which emphasizes speed, informality, and friendliness, on customer satisfaction. The study highlights the importance of personal interaction between baristas and customers, which fosters a closer relationship and enhances the overall customer experience. Key elements of Kopi Boy's service include fast service, customer engagement in the coffee-making process, and a relaxed atmosphere that promotes comfort and satisfaction. Additionally, Kopi Boy maintains consistency in product quality and incorporates creativity through unique menu offerings and latte art. The study also examines Kopi Boy's strategies for improving customer service, such as employee training, service personalization, menu innovation, and technology implementation. These strategies are designed to enhance the customer experience, build loyalty, and strengthen the brand's competitive edge. The research concludes that by focusing on personal connections, service efficiency, innovation, and community involvement, Kopi Boy can continue to deliver superior service and foster strong relationships with customers, ultimately expanding its customer base and creating a vibrant community around the brand.